Regulatory Resources of Professional Self-Determination in Students Under Stress: Research Approaches and Theoretical Foundations - Varvara I. Morosanova; Nailya G. Kondratyuk; Anna M. Potanina (Lomonosov Moscow State University, 2024)
Background. The relevance of the study is due to the need for investigating the professional development of senior schoolchildren and students under the conditions of increasing influence of stress factors. Objectives. The study set the purpose to review and analyze modern scientific ideas on the problem of psychological resources of professional self-determination in students under stress. Methods. Search for and analysis of recent theoretical and empirical research publications was carried out. Abstraction, and generalization of obtained data relevant to the topic of the article were applied. Methods also included identification of theoretical foundations and promising directions for research into the problem of psychological resources of professional self-determination of students under stress. Results. Analysis of the recent publications allowed to reveal conceptual differences in understanding the phenomenon of professional self-determination of the individual. It identified a variety of approaches to the study of human professional behaviour. The authors highlighted and characterized the main directions of modern research on the topic discussed, indicating the demand for studying human professional behaviour in the changing conditions of life. The study systematized theoretical foundations and empirical data on the psychological resources for students' professional self-determination and for overcoming life stress. Conclusions. The study revealed the potential of a resource-based approach to the study of the stress influence on the professional self-determination of students and substantiated the role of conscious self-regulation resources in choosing and mastering a profession.